Superplastic forming of a three-stage hemispherical 5083 aluminium profile - Balasubramanian, Muthusamy (Strojniški vestnik, 2015)
Three-stage superplastic blow forming characteristics of 5083 aluminium sheets in a hemispherical die cavity have been studied as a function of forming pressure, die entry radius, coefficient of friction, forming time and forming height, both experimentally and using finite element method in this work. Optimum forming pressure for achieving uniform thickness in a complex three-stage radius dome profile has been established. Variations in thickness profile are observed experimentally and in FEM analysis in three different die entry regions. The thickness profile has also been predicted as a function of the friction coefficient and die entry radius. The changes in pole thickness, relative height and relative radius of the profile along with the thinning factor are discussed.
Keywords: aluminijeve zlitine 5083; eksperimenti; finite element method; metoda končnih elementov; postopek superplastičnega preoblikovanja; tristopenjska polkrogelna kupola